2018
DOI: 10.3390/ijns4010008
|View full text |Cite
|
Sign up to set email alerts
|

Raising Awareness of False Positive Newborn Screening Results Arising from Pivalate-Containing Creams and Antibiotics in Europe When Screening for Isovaleric Acidaemia

Abstract: While the early and asymptomatic recognition of treatable conditions offered by newborn screening confers clear health benefits for the affected child, the clinical referral of patients with screen positive results can cause significant harm for some families. The use of pivalate-containing antibiotics and more recently the inclusion of neopentanoate as a component within moisturising creams used as nipple balms by nursing mothers can result in a significant number of false positive results when screening for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…After surveying mothers, it was concluded that the FP results were caused by the use of a nipple fissure cream used by lactating mothers. These findings were also reported by other European neonatal screening programs [ 34 ]. After the implementation of 2TT for C5 isomers, the number of FPs for IVA decreased to zero ( Table 6 ), which makes the impact of the secondary biomarker clear.…”
Section: Resultssupporting
confidence: 89%
“…After surveying mothers, it was concluded that the FP results were caused by the use of a nipple fissure cream used by lactating mothers. These findings were also reported by other European neonatal screening programs [ 34 ]. After the implementation of 2TT for C5 isomers, the number of FPs for IVA decreased to zero ( Table 6 ), which makes the impact of the secondary biomarker clear.…”
Section: Resultssupporting
confidence: 89%
“…66 For instance, the personalised infant-WBMs could support newborn screening for IVA, which is suffering from an increasing number of false-positive screening results, due to antibiotics given to pregnant women to treat urinary tract infections 74 and pivalate-containing creams. 75 Moreover, drug dosage determination for children is very important as their immature drug metabolism is often associated with drug toxicity 76 and the pharmacokinetics and pharmacodynamics of drugs are often different in children and adults. 77, 78 However, almost 50% of prescription drugs lack age-appropriate dosing guidelines 76 and the paediatric drug clearance data is less attainable, which is probably due to the difficulties associated with conducting paediatric clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that exogenous sources of pivalic acid and the subsequently formed isomeric compound pivaloylcarnitine can cause a false‐positive result, 7 and therefore, methods to differentiate pivaloyl‐ from isovalerylcarnitine in NBS both for derivatized 8,9 and nonderivatized 10,11 samples have been suggested in the past. Pivalic acid containing antibiotics have caused trouble in NBS before and problems in other parts of Europe have been reported 11,12 . Similar to antibiotics and as well for pharmacokinetic reasons, leukocyte elastase inhibitors have been bound to pivalic acid and have caused false‐positive IVA screening 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Pivalic acid containing antibiotics have caused trouble in NBS before and problems in other parts of Europe have been reported. 11 , 12 Similar to antibiotics and as well for pharmacokinetic reasons, leukocyte elastase inhibitors have been bound to pivalic acid and have caused false‐positive IVA screening. 13 Pivalic acid derivatives are also used by the cosmetic industry as emollient under the term “neopentanoate” and neopentanoate‐esters in a nipple‐fissure unguent that was routinely provided to breastfeeding mothers resulted in a high number of false‐positive screening cases in Belgium.…”
Section: Discussionmentioning
confidence: 99%